Manajemen Sarana Dan Prasarana Dalam Peningkatan Proses Pembelajaran Di SMP Negeri 1 Perak Jombang - Devianti; Dita Dzata Mirrota (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2021)
This study aims to: 1).Describe the management of facilities and infrastructure in SMP Negeri 1 Perak Jombang 2).Describe the management of facilities and infrastructure in improving the learning process at SMP Negeri 1 Perak Jombang. The method used is a qualitative method with a qualitative descriptive design with data collection techniques through observation, interviews, and documentation. Furthermore, data analysis was carried out using descriptive qualitative analysis. The results showed that 1). Management of infrastructure facilities at SMP Negeri 1 Perak Jombang which consists of certain steps systematically, namely: a) Planning is carried out at the beginning of each new school year. The need for facilities and infrastructure, implementation, and the person in charge is stated in the RKAS. Financing in determining the need for facilities and infrastructure is made on a priority scale. b) Procurement of facilities and infrastructure is usually carried out to repair damaged items and submit a proposal to the Office for the repair program. c) Distribution of existing facilities and infrastructure allocates distribution, if there are goods, they can be distributed according to the parties in need. d) Inventory is carried out recording all learning facilities and infrastructure owned by the school. d) Elimination of infrastructure that is not suitable for use by removing it 2). Management of facilities and infrastructure in improving the learning process at SMP Negeri 1 Perak Jombang that the management of facilities and infrastructure is optimal and adequate facilities and infrastructure are able to improve the learning process. As for good management, it has created a conducive classroom atmosphere, an active learning atmosphere.